Low-Dose Collagenase Chemonucleolysis Combined with Radiofrequency in the Treatment of Lumbar Disc Herniation: A 10-Year Retrospective Study. (23rd December 2021) - Wang, Meng; Zhang, Xuexue; Yu, Yaoping; Xu, Gang; Nie, Jinping; Yu, Bo; Cao, Xuezhong; Qiu, Mizhen; Liao, Yunhua; Zhang, Daying; Yan, Yi
Abstract : Objective . This study explored the 10-year efficacy, safety, and prognostic factors of low-dose collagenase chemonucleolysis (CCNL) combined with radiofrequency (RF) in the treatment of lumbar disc herniation (LDH). Methods . The data of 167 LDH patients were collected. Modified MacNab criteria, Numerical Rating Scale (NRS), and Japanese Orthopedic Association (JOA) scores were, respectively, used to evaluate patients' excellent and good rates, pain degree, and nerve function. The preoperative and 10-year postoperative patients' pain, numbness, and muscle weakness were compared. Patients' complications in perioperative period, recurrent/reappeared LDH, and reoperations were recorded. Finally, the independent risk factors affecting the long-time efficacy were assessed. Results . A total of 126 patients were included. The patients' excellent and good rates were 86.51%–92.86% with no significant difference P > 0.05 . Postoperative NRS and JOA scores significantly improved P < 0.01, most obvious within 6 months postoperatively. At 10 years postoperatively, 65.08%, 83.95%, and 93.02% of patients' pain, numbness, and muscle weakness were completely relieved P < 0.05 . Perioperative complications occurred in three patients with the rate of 2.38%. Recurrent/reappeared LDH patients were 11 with the ratio of 8.73%; nine of them underwent reoperations with the rate of 7.14%. And patients' probability of fair and poor efficacy at 10 years postoperatively with the course of disease >12 months and the responsibility disc ≥2 were, respectively, 6.005 and 4.227 times that of patients with the course of disease ≤12 months and the responsibility disc = 1 P < 0.05 . Conclusion . The combined treatment is effective and safe in the long term. A course of disease > 12 months and responsibility disc ≥2 independently reduce efficacy, and a course of disease > 12 months has a more significant impact.